2021
DOI: 10.1136/bcr-2021-243696
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry pink blood: hypertriglyceridaemia and diabetic ketoacidosis secondary to poorly controlled type 2 diabetes mellitus

Abstract: A 54-year-old woman with insulin-requiring type 2 diabetes mellitus presented with acute shortness of breath and drowsiness on a background of polydipsia, weakness and significant weight loss. One year ago, she had decided to stop her insulin and other medications and adopt lifestyle modifications instead. Initial emergency department (ED) blood samples were highly lipaemic and appeared strawberry pink. She was eventually diagnosed with diabetic ketoacidosis (DKA) with severe hypertriglyceridaemia, intubated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Reports on severe hypertriglyceridemia associated with sirolimus treatment are rare, however have to be considered amongst the differential diagnoses (Box 1). Literature searches revealed that levels that high as in our index case have not been observed before [23][24][25]. Comingling of the red blood cells with the white appearing triglycerides are responsible for the phenomenon of pink colored blood [26].…”
Section: Discussionmentioning
confidence: 46%
“…Reports on severe hypertriglyceridemia associated with sirolimus treatment are rare, however have to be considered amongst the differential diagnoses (Box 1). Literature searches revealed that levels that high as in our index case have not been observed before [23][24][25]. Comingling of the red blood cells with the white appearing triglycerides are responsible for the phenomenon of pink colored blood [26].…”
Section: Discussionmentioning
confidence: 46%
“…Plasma is cloudy and milky-colored in individuals who donate Blood after eating a fatty breakfast (15). A lipemic Blood sample is the color of strawberry milkshake, and the plasma is milky white due to the presence of fat particles (16,17). A cherry-colored plasma indicates hemolysis (15).…”
Section: Blood Colormentioning
confidence: 99%
“…In bacterial infections, the color of Blood changes to dark crimson or black (15,17). When dealing with abnormal Blood color in a critically-ill patient, differential diagnoses include cyanide poisoning, dyshemoglobinemias (e.g., methemoglobinemia and carboxyhemoglobin), lipemia and drug overdose should be considered (16). The color of menstruation Blood can be black, red-brown/black, light red, pink, orange or gray.…”
Section: Blood Colormentioning
confidence: 99%